Highlights of children with Cancer UK’s workshop on drug delivery in paediatric brain tumours - Nailor, Audrey; Walker, David A.; Jacques, Thomas S.; Warren, Kathy E.; Brem, Henry; Kearns, Pamela R.; Greenwood, John; Penny, Jeffrey I.; Pilkington, Geoffrey J.; Carcaboso, Angel M.; Fleischhack, Gudrun; Macarthur, Donald; et al. (Cancer Intelligence, 2016)
The first Workshop on Drug Delivery in Paediatric Brain Tumours was hosted in London by the charity Children with Cancer UK. The goals of the workshop were to break down the barriers to treating central nervous system (CNS) tumours in children, leading to new collaborations and further innovations in this under-represented and emotive field. These barriers include the physical delivery challenges presented by the blood–brain barrier, the underpinning reasons for the intractability of CNS cancers, and the practical difficulties of delivering cancer treatment to the brains of children. Novel techniques for overcoming these problems were discussed, new models brought forth, and experiences compared.